The knowledge manager's handbook : a step-by-step guide to embedding effective knowledge management in your organization - Milton, N. J. (Nick J.); Lambe, Patrick, 1960 (London : Philadelphia : Kogan Page, 2016)
"The way an organization manages and disseminates its knowledge is key to informed decision making, effectiveness, and maintaining a competitive edge. Companies need a knowledge management framework that is customized to their particular needs and priorities. Nick Milton and Patrick Lambe draw on their experience as consultants and project leaders to act as guides through each stage of creating and defining an effective knowledge management framework. Taking into account people, processes, technologies, and governance, they show how each of these components can be optimized to unlock knowledge from the company and make a sustainable change in the organization's knowledge management culture. "--
"The way an organization manages and disseminates its knowledge is key to informed business decision-making, effectiveness and competitive edge. Because knowledge management is not a one-size-fits-all method, you need a framework tailored to your organization and its priorities. The Knowledge Manager's Handbook takes you step by step through the processes needed to define and embed an effective knowledge management framework within your organization. Knowledge management experts Nick Milton and Patrick Lambe draw on their practical experience as consultants and project leaders to guide you through each stage of creating and implementing a knowledge management framework to answer your organization's specific needs. The framework takes into account the four essential aspects of knowledge management - people, processes, technologies and governance - and shows how each of these can be optimized to unlock the value of your organization's knowledge. With international case studies from organizations of all sizes and sectors, and user-friendly templates and checklists to help you implement effective knowledge management procedures, The Knowledge Manager's Handbook is the end to end guide to making a sustainable change in your organization's knowledge management culture"--
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Knowledge management; BUSINESS & ECONOMICS / Information Management; BUSINESS & ECONOMICS / Knowledge Capital; BUSINESS & ECONOMICS / Management